Wnt directs the endosomal flux of LDL‐derived cholesterol and lipid droplet homeostasis. (7th April 2015) - Scott, Cameron C; Vossio, Stefania; Vacca, Fabrizio; Snijder, Berend; Larios, Jorge; Schaad, Olivier; Guex, Nicolas; Kuznetsov, Dmitry; Martin, Olivier; Chambon, Marc; Turcatti, Gerardo; Pelkmans, Lucas; et al.
Abstract The Wnt pathway, which controls crucial steps of the development and differentiation programs, has been proposed to influence lipid storage and homeostasis. In this paper, using an unbiased strategy based on high‐content genome‐wide RNAi screens that monitored lipid distribution and amounts, we find that Wnt3a regulates cellular cholesterol. We show that Wnt3a stimulates the production of lipid droplets and that this stimulation strictly depends on endocytosed, LDL‐derived cholesterol and on functional early and late endosomes. We also show that Wnt signaling itself controls cholesterol endocytosis and flux along the endosomal pathway, which in turn modulates cellular lipid homeostasis. These results underscore the importance of endosome functions for LD formation and reveal a previously unknown regulatory mechanism of the cellular programs controlling lipid storage and endosome transport under the control of Wnt signaling.